2019
DOI: 10.3390/biom9120787
|View full text |Cite
|
Sign up to set email alerts
|

Betulinic Acid Attenuates T-2-Toxin-Induced Testis Oxidative Damage Through Regulation of the JAK2/STAT3 Signaling Pathway in Mice

Abstract: T-2 toxin is one of the most toxic type A trichothecene mycotoxins in nature, and it exhibits reproductive toxicity. Betulinic acid (BA) is a natural pentacyclic triterpene compound found in species of Betula, and it has been reported to have antioxidant activity. The aim of the present study was to investigate the protective effect of BA on T-2-toxin-induced testicular injury in mice and explore its molecular mechanism. Sixty adult male mice were randomly divided into groups. The mice were pretreated orally w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 42 publications
(35 reference statements)
0
29
0
Order By: Relevance
“…Subsequently, we wanted to examine the molecular mechanism of pancreas injury. Considering that the Stat3, MAPK, and Akt-mTOR pathways play a prominent role in oxidative stress, inflammatory response, and cell apoptosis 33 , 34 , we measured the levels of Stat3, p38/JNK, mTOR and their corresponding phosphorylated protein expression. Importantly, the results showed that the mice of the STZ+circPPM1F group exhibited significantly enhanced levels of phosphorylated Stat3, p38, and JNK expression compared with control, STZ and STZ+pZW1 groups.…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, we wanted to examine the molecular mechanism of pancreas injury. Considering that the Stat3, MAPK, and Akt-mTOR pathways play a prominent role in oxidative stress, inflammatory response, and cell apoptosis 33 , 34 , we measured the levels of Stat3, p38/JNK, mTOR and their corresponding phosphorylated protein expression. Importantly, the results showed that the mice of the STZ+circPPM1F group exhibited significantly enhanced levels of phosphorylated Stat3, p38, and JNK expression compared with control, STZ and STZ+pZW1 groups.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, research has shown that intraperitoneal injection of T-2 toxin also causes oxidative stress [ 31 ]. Our previous study found that intraperitoneal injection of 4 mg/kg T-2 toxin could cause oxidative damage in testicular tissue [ 32 ]. Based on these studies, an intraperitoneal injection of 4 mg/kg T-2 toxin was used to establish an oxidative damage model of the thymus in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Fifty male Kunming mice (4–5 w) were provided by Hunan Silaike Jingda Laboratory Animal Co., Ltd. (Changsha, Hunan, China). The duration of treatment and the doses of T-2 toxin and BA were chosen from previous studies and preliminary experiments [ 23 , 32 ]. The mice were placed individually in a room with controlled humidity (50–70%) and temperature (22–25 °C).…”
Section: Methodsmentioning
confidence: 99%
“…Besides, some reports revealed that betulinic acid could regulate STAT3 in many cancer types [51,52]. In central nervous system cancer cell lines, compounds nakiterpiosin and cucurbitacin I had a positive correlation coefficient greater than 0.3 (higher expression of STAT3 related to resistance).…”
Section: Stat3 Expression and Drug Responsementioning
confidence: 99%